PELAKSANAAN RETRIBUSI JASA USAHA PADA PENJUALAN PRODUK HASIL USAHA DAERAH PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI BALI - Made Ananda Dwi Ervaden; Ibrahim R.; I Ketut Suardita (Kertha Negara : Journal Ilmu Hukum, 2013)
Bali Provincial Government seeks to improve the quality and quantity of publicservices by the issuance of Bali Provincial Regulation No. 3 years of 2011 on BusinessRetributions are therein expressly set about setting sales levy local business results,including products of local business provided by Department of Marine and Fisheriesof Bali. This rule is expected to fixed accommodative by reference to Law No. 32 yearsof 2004 on Regional Governance. Next can be formulated, How does implementation ofRetributions collection of business services on local businesses selling products toDepartment of Marine and Fisheries of Bali and What is the problem in theimplementation of Business Service Retribution on Department of Marine and Fisheriesof Bali. This writing uses an empirical research method to discuss the issue. Last, canbe concluded that the implementation of collection of this Retributions conducted byBali Provincial Regulation No. 3 of 2011 and The constraints faced in collecting of thisRetribution has not capable resolved by the government of Bali, so the contribution ofthe Retribution to improving local revenue in implementing of regional autonomy in theprovince of Bali is still less than the maximum.